Effects of self selection in architectural design process (ADP) ; considering user centered design (UCD) / Mahdi Torabi, Mahmud Mohd Jusan and Alireza Daneshpour - Torabi, Mahdi; Mohd Jusan, Mahmud; Daneshpour, Alireza (2012)
Diversity of human requirements in his living environment is obvious. Architecture ideal is to respond such varied requirements. The Architectural Design Process (ADP) which has been defined for this basic purpose aims at fulfilling not only physical and functional but also psychological human necessities.Recent trends in architectural design show that in most of the cases, the focus of ADP has been shifted to the business goals, fancy features and technological capabilities. Even if none of these approaches can be blamed, what has been lost here is a mere respect to human values. In this regard, paying attention to end-users' ideas, believes, attitudes and desires, which has been named self-selection in this paper,can be considered as an appropriate method for deriving final users' values. In fact, User-Centered Design (UCD) is a format of self-selection which focuses on designer's side. UCD attaches importance to architectural plan as an output.This type of architectural plan tries to adopt to final users' requests, wishes, feelings, behaviors and life styles. Inspired by the concept, some different methods have been created. Designing according to UCD principles and basics contributes to architectural plan to be more satisfactory and desirable by the users since they would able to realize their ideas. In addition, this kind of ADP encourages end-users to personalize more eagerly their surrounding built environment. Ultimately, the users would feel more comfortable and convenient in his living space. In this respect, not only designers but also the users share the same amount of satisfaction.